Analysis of the Design of Islamic Religious Education Learning Assessment in the Merdeka Curriculum at SMP 9 Muhammadiyah Gondanglegi - Fikra, Dzakiyah; Maisaroh, Ajeng; Zuhriyah, Indah Aminatuz (Edumaspul: Jurnal Pendidikan, 2023)
Assessment or evaluation is an integral and inseparable part of learning. Through assessment, an individual’s abilities become clearly visible. The purpose of writing this article is to describe the design of PAI and BP learning assessments in the Merdeka Curriculum at SMP 9 Muhammadiyah Gondanglegi as one of the schools that has implemented the Merdeka Curriculum with the Mandiri Berubah option. This research is a qualitative research using a descriptive method. The data collection techniques involve interviews and documentation. Data processing is carried out through validity testing and data triangulation across time, place, and subjects. The results of this research indicate that the design of PAI and BP learning assessments at SMP 9 Mugi follows a sequence from planning, implementation, data analysis, data interpretation, and follow-up. The forms of assessment conducted are Diagnostic Assessment, Formative Assessment, and Summative Assessment. Assessment greatly assists teachers in reflecting on the teaching strategies they employ